PENERAPAN PROGRAM MAGRIB MENGAJI UNTUK MENUMBUHKAN SPIRIT ANAK MENCINTAI AL-QURAN DI RW 05 DESA KERTAWINANGUN - rusli; deni ariyanto; Ahmad Agisna; Mudzakkir Amin (IAIC (Institut Agama Islam Cirebon), 2023)
Based on observations, it was found that the implementation of the Maghrib Koran program carried out by group 1 Kertawinangun Village RT 22 RW 05 Kedawung District, Cirebon Regency can be said to be good, but there are still some students in reading the Qur'an who are still not fluent in reciting the Qur'an. 'an. This is influenced by various factors. One of the most dominant factors is the lack of parental encouragement as the main motivator so that children are enthusiastic in going to the Koran and studying the Qur'an, and the absence of a generation of teachers who continue the Maghrib Koran activities. We hope that after this service activity is completed in the future there will be others who will continue the next generations of Al-Qur'an teachers. So that the mosque is not only a place for worship, but also as a center of education.